Staphylococcus aureus infection and disease - Honeyman, Allen; Friedman, Herman, 1931-2007; Bendinelli, Mauro (Infectious agents and pathogenesis., 2001)
Staphylococcus aureus is now acknowledged as being the most important bacterial pathogen of humans. It usually produces localized disease but can be rapidly invasive, spreading through the tissues, invading bone, and seeding the bloodstream to produce a fulminant picture of septic shock, disseminated intravascular coagulation, and rapid death. Moreover, most strains of staph infections are becoming resistant to most antibiotics, thus posing a significant problem for hospitals and health care facilities.